3D Printing Parameters Of Acrylonitrile Butadiene Styrene Polymer For Friction And Wear Analysis Using Response Surface Methodology - Abdollah, Mohd Fadzli; Amiruddin, Hilmi; Ramli, Faiz Redza; Tamaldin, Noreffendy; Mohamad Norani, Mohamad Nordin; Abdullah, Muhammad Ilman Hakimi Chua (SAGE Publications, 2020)
This study intends to analyse the coefficient of friction and wear properties of the acrylonitrile butadiene styrene polymer by determining the optimal parameters for 3D printing. The pin specimens were produced using the fused filament fabrication 3D printing. Response surface methodology is used for the multivariate analysis, and Box–Behnken Design is the chosen symmetrical design method. Changes to the dependent variables, coefficient of friction and wear rate, were analysed as a function of the nozzle temperature, layer height and printing pattern. The coefficient of friction and wear rate were measured using a pin-on-disc tribometer. A good agreement between the modelled and measured values of coefficient of friction and wear rate was observed. The study suggests that layer height affecting coefficient of friction and wear rate most significantly. It is determined that a layer height of 0.10 mm and a nozzle temperature of 234C using the triangle printing pattern is the optimal set of combination to minimise coefficient of friction and wear rate.